"Treaty Principles": Constitutional Relations Inside a Conservative Jurisprudence - McHugh, PG (Victoria University of Wellington Law Review, 2008)
This article looks at the impact and afterlife of the groundbreaking Maori Council judgments handed down in the late 1980s by the Court of Appeal presided by the late Sir Robin Cooke (as he then was). This article refutes any notion of constitutional relations with Māori being founded on race despite unilateral (and long discarded) legal design tending towards that characterisation. The true pattern has been iwi-based and it has arisen from the continuity of whakapapa in the organization of Maori political life and relations with the state notwithstanding meddlesome but ultimately ineffectual legislative attempts to dilute tribalism. Over the past twenty plus years, the Treaty claims processes initiated in 1985 have accentuated and revitalised that tribalism. Far from licensing judicial interventionism "Treaty principles" are part of an embedded and conservative jurisprudence of Māori affairs. Their elimination from legislation would amputate a major segment of that jurisprudence. The courts, whose profile in this broad field (Treaty claims processes most notably) is mostly a resiling one, would respond by generating their own version. The legacy of Sir Robin Cooke’s court is deep-rooted and thoroughly integrated into the New Zealand legal system.